2016
DOI: 10.1642/auk-15-175.1
|View full text |Cite
|
Sign up to set email alerts
|

Wing size-related reed habitat selection by Great Reed Warbler (Acrocephalus arundinaceus) males

Abstract: In this study we explored the linkage between wing size of Great Reed Warbler males (Acrocephalus arundinaceus) and their habitat selection and relate these linkages to differences in reed habitat quality. We measured the wing sizes of males nesting in 6 different reed habitats. To explain reed habitat selection, we modeled male wing size as a function of 7 predictor variables describing reedbeds: proportion of managed reed; densities of mixed, old, and fresh reed; reed stem diameter; water depth; and fluctuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 17 publications
2
22
0
Order By: Relevance
“…The importance of water depth for the nesting of the Great Reed Warbler was previously reported as a factor that can characterize the quality of a reed habitat (Graveland 1998, Mérő et al 2016. We confirm the results of previous studies that nest density was related to water depth ; however, Dyrcz (1981) and reported that nest density can also depend on reed structure.…”
Section: Discussionsupporting
confidence: 91%
“…The importance of water depth for the nesting of the Great Reed Warbler was previously reported as a factor that can characterize the quality of a reed habitat (Graveland 1998, Mérő et al 2016. We confirm the results of previous studies that nest density was related to water depth ; however, Dyrcz (1981) and reported that nest density can also depend on reed structure.…”
Section: Discussionsupporting
confidence: 91%
“…In a previous comparison of male wing size over six habitat types (Mérő et al 2016), we found that male wing length was highest along large canals (presumed high-quality habitats), intermediate in mining ponds and middlesized canals, and was lowest in marshes and small canals. We also found evidence that reed (Phragmites australis) habitats attractive to males were those with deep, stable water and little reed management (Mérő et al 2016). Habitat choice by females may correspond to or contradict these patterns.…”
Section: Introductionmentioning
confidence: 67%
“…Long-winged, probably older, males arrive back to the breeding grounds earlier and occupy territories in the presumably highestquality habitats, and later-arriving, usually younger, males probably settle in habitats of lower quality (Hasselquist 1998, Leisler andSchulze-Hagen 2011). In a previous comparison of male wing size over six habitat types (Mérő et al 2016), we found that male wing length was highest along large canals (presumed high-quality habitats), intermediate in mining ponds and middlesized canals, and was lowest in marshes and small canals. We also found evidence that reed (Phragmites australis) habitats attractive to males were those with deep, stable water and little reed management (Mérő et al 2016).…”
Section: Introductionmentioning
confidence: 97%
“…As an example, a very fine-scaled study on Great Reed Warbler in Serbia, found that maintaining different water depth in the reedbed differently affected the survival probability of juveniles, males and females respectively (Méro et al 2018). In the same study site, it has been observed that biggest, putatively dominant, Great Reed Warblers preferentially establish breeding territory in unmanaged (but flooded) portions of the reedbed, while smaller individuals mainly occupy portions of the reedbed in which winter harvesting and burning are practised (Méro et al 2017). The maintenance of a range of different micro-habitats within a reedbed (i.e.…”
Section: Discussionmentioning
confidence: 92%